Longer Cortical Silent Period Length Is Associated to Binge Eating Disorder: An Exploratory Study - Antunes, Luciana C.; Elkfury, Jessica Lorenzzi; Parizotti, Cristiane Schultz; Brietzke, Aline Patrícia; Bandeira, Janete Shatkoski; Torres, Iraci Lucena da Silva; Fregni, Felipe; Caumo, Wolnei (Frontiers in Psychiatry, 2020)
Introduction: Although binge eating disorder (BED) is an eating disorder and obesity is a clinical disease, it is known that both conditions present overlapped symptoms related to, at least partially, the disruption of homeostatic and hedonistic eating behavior pathways. Therefore, the understanding of neural substrates, such as the motor cortex excitability assessed by transcranial magnetic stimulation (TMS), might provide new insights into the pathophysiology of BED and obesity. Objectives: (i) To compare, among BED, obesity, ex-obese, and HC (healthy control) subjects, the cortical excitability indexed by TMS measures, such as CSP (cortical silent period; primary outcome), SICI (intracortical inhibition), and ICF (intracortical facilitation; secondary outcome). (ii) To explore the relationship of the CSP, eating behavior (e.g., restraint, disinhibition, and hunger), depressive symptoms, and sleep quality among the four groups (BED, obesity, ex-obese, and HC). Methods: Fifty-nine women [BED (n = 13), obese (n = 20), ex-obese (n = 12), and HC (n = 14)] comprise the total sample for this study. Assessments: cortical excitability measures (CSP, SICI, and ICF), inhibition response task by the Go/No-go paradigm, and instruments to assess the eating psychopathology (Three-Factor Eating Questionnaire, Eating Disorder Examination Questionnaire, and Binge Eating Scale) were used. Results: A MANCOVA analysis revealed that the mean of CSP was longer in the BED group compared with other three groups: 24.10% longer than the obesity group, 25.98% longer than the HC group, and 25.41% longer than the ex-obese group. Pearson's correlations evidenced that CSP was positively associated with both eating concern and binge eating scores. Conclusion: The findings point out that BED patients present longer CSP, which might suggest an upregulation of intracortical inhibition. Additionally, CSP was positively correlated with Binge Eating Scale and eating concern scores. Further studies are needed.